Dream a World Anew: The African American Experience and the Shaping of America - Kinshasha Holman Conwill (Smithsonian Books, 2016)
Dream A World Anew is the stunning gift book accompanying the opening of the Smithsonian National Museum of African American History and Culture. It combines informative narratives from leading scholars, curators, and authors with objects from the museum's collection to present a thorough exploration of African American history and culture. The first half of the book bridges a major gap in our national memory by examining a wide arc of African American history, from Slavery, Reconstruction, the Harlem Renaissance, and the Great Migrations through Segregation, the Civil Rights Movement, and beyond. The second half of the book celebrates African American creativity and cultural expressions through art, dance, theater, and literature. Sidebars and profiles of influential figures--including Harriet Tubman, Robert Smalls, Ida B. Wells, Mordecai Johnson, Louis Armstrong, Nina Simone, and many others--provide additional context and interest throughout the book. Dream a World Anew is a powerful book that provides an opportunity to explore and revel in African American history and culture, as well as the chance to see how central African American history is for all Americans.